Exploration on the optimization of occupational injury and employment protection of takeout workers in the context of public health - Wang, Qifan; Liu, Qingyu; Zhu, Tianyi (Frontiers in Public Health, 2023)
With the acceleration of the pace of urban life and the development of information technology, the takeout industry has emerged as the times require, which obtains intermediate costs by distributing goods to consumers. People pay more and more attention to public health, which requires takeout workers to drive as fast as possible to ensure the quality and safety of goods, but it also makes takeout workers suffer from various occupational injuries, such as car accidents, stomach diseases caused by eating disorders and long-term psychological pressure. This paper optimized the employment protection of takeout workers in combination with their professional characteristics. This paper used the analytic hierarchy process (AHP) to analyze the indicators that can evaluate the optimization effect of employment protection for takeout workers, and compared the occupation of takeout workers before and after employment protection. The experimental results showed that in Meituan takeout, the rationality of the average delivery management system before and after the optimization of employment protection was 47.2 and 64.4%, respectively; in ELEME takeout, the rationality of the average takeout distribution management system before and after the optimization of employment protection was 55.0% and 69.8%, respectively. Therefore, in the context of public health, the implementation of social security, employment relationship and optimization of service evaluation mechanism for outbound sales personnel can effectively improve the rationality of the delivery management system.